Analysis of The “Coffee Cyanide” Case: Unveiling Judicial Decisions From A Constructivist Paradigm Perspective - Febriyani, Emiliya; Tantimin, Tantimin; Alhakim, Abdurrakhman; Jaya, Febri (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2023)
The judicial verdict fundamentally embodies the effort of legal enforcement to actualize the ideals of justice, certainty, and utility. It stands as the culmination of the paradigm believed by the judiciary. This study scrutinizes the judicial considerations within the constructivist paradigm, focusing on the case of cyanide coffee. Conducted qualitatively, this research delves into conceptual ideas examining the guidelines for legal discovery by judges in cases of premeditated murder involving cyanide coffee, employing a paradigmatic analysis through the lens of legal philosophy. The findings reveal that judicial decisions in cyanide coffee cases within the constructivist paradigm have yet to fully reflect a sense of justice. Therefore, legal efforts are imperative to instill a sense of fairness within society.